O Perfil Profissional Do Controller E As FunAAes De Controladoria: Um Estudo Da Atual Necessidade Do Mercado De Trabalho (Global Journal of Management and Business Research, 2014)
The objective of the study was to analyze the current profile professional skills and abilities required for a controller in the levels of management and supervision as well as investigate whether the profile of this professional association is the size of the company, their source of capital hierarchy from office, academic and salary offered by the current labor market. It searched to identify the requirements for contractors, through the listings of selection and recruitment companies online. We used 295 valid announcements and information were dealt with content analysis, and validated by means of nonparametric statistics chi-square and Fisher's exact test. The significance level was used 10% (α = 0.10) which makes the confidence interval of 90%. The data were organized in Profile technical, managerial and behavioral.
Keywords: professional profile controller functions